Performance Analysis of the Sporadic Server Implementation in Real-Time Specification for Java - Tripode, Carlos; Santos, Rodrigo; Orozco, Javier (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2011)
In this paper, we introduce the implementation of the Sporadic Server algorithm at the user level in Real Time Java. That is, we do not modify the specification of the Java Virtual Machine (JVM) so our proposal runs without problems on every JVM with support for real-time scheduling. The paper includes an experimental evaluation of the aperiodic handling mechanism using as benchmark the one developed for the RTSJ.